Different flowsheets isoenergetic manifolds being generated in methanol – propylacetate – toluene extractive distillation with aniline. - B. B. Dolmatov; A. V. Timoshenko; A. G. Volkov; E. A. Anokhina (Тонкие химические технологии)
This work is devoted for investigation of isocriterial manifolds and isocriterial fields arrangement into initial feed composition simplex. That fields and manifolds dividing of them are formed at methanol - n-propylacetat - toluene with aniline extractive distillation. Initial mixture contains one binary azeotrop with minimum boiling point (in methanol - toluene pair) and one tangential azeotrop in methanol - n-propylacetat pair near the pure n-propylacetat. In the capacity of the optimization criteria was chosen heating capacities on the distillation columns reboilers.